(untitled) (Journal of Pathology of Nepal, 2018)
IgA nephropathy is one of the commonest forms of primary glomerulonephritis in the world, most commonly among Asian population. Though usually slowly progressive, it is one of the important causes of chronic renal failure. Abnormal IgA1 are formed which leads to formation of IgG antibodies which deposit in the mesangium. It presents with synpharyngitic hematuria and can have variable histopathological patterns. The Oxford classification was devised in order to categorize the histopathological patterns, correlate with clinical course and modify treatment accordingly. Different histopathological criteria are assessed in the classification, which include mesangial proliferation (M), endocapilary proliferation (E), segmental sclerosis (S), and interstitial fibrosis/tubular atrophy (T).The classification has become widely accepted around the world but still needs further validation studies and incorporation of newer parameters.